Pengaruh Ukuran Perusahaan, Pertumbuhan Penjualan, Struktur Aktiva dan Risiko Bisnis Terhadap Struktur Modal - Kurniawati , Indah Ayu (Economics and Digital Business Journal, 2024)
The purpose of this study was to determine the effect of Current Ratio, Debt to Equity Ratio, Return on Investment and Firm Size on Firm Value. The population used is public companies in the Automotive and Automotive Components sub-sector which are listed on the Indonesia Stock Exchange for the 2018-2022 period and the sample in this study was 12 out of 15 companies. This research model uses multiple linear analysis which is processed using SPSS version 22. The results of this study show that simultaneously Current Ratio, Debt to Equity Ratio, Return on Investment, and Firm Size have a significant effect on Firm Value. The results showed that Return on Investment partially has a positive effect on Firm Value, while Current Ratio, Debt to Equity Ratio and Firm Size partially have no effect on Firm Value